Hubungan Stres Kerja Dengan Kecelakaan Kerja Pada Pekerja Di Bagian Pemanen Kelapa Di PT.X Di Desa Tial Kabupaten Maluku Tengah Provinsi Maluku - Zulfikar Lating; Ira Deseilla Pawa (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Work stress is one of the main concerns regarding occupational health and safety for the workforce's well-being and health issues. It has been estimated that half of the workforce's absences and occupational accidents at work were caused by work-related stress disruptions. This research aimed to find out the relationship between work stress and occupational accident in the workforce of the harvester palm oil unit. This research was an observational analytic research with a cross-sectional approach. The result of this research showed that there is a positive relationship between work stress and the risk of occupational accidents. Statistical analysis using the Chi-Square test obtained a p-value of 0.005 compared to the degree of significance (p-value <0.05). The recommendations for the company could be used as a reference to train the occupational health and safety workers unit to increase awareness of occupational health and safety.